2021
DOI: 10.3389/fmicb.2021.680060
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Antifungal Susceptibility Analysis of Stephanoascus ciferrii Complex Species Isolated From Patients With Chronic Suppurative Otitis Media

Abstract: BackgroundStephanoascus ciferrii is a heterothallic ascomycetous yeast-like fungus. Recently, the concept of S. ciferrii complex has been proposed and it consists of S. ciferrii, Candida allociferrii, and Candida mucifera. We aimed to identify 32 strains of S. ciferrii complex isolated from patients with chronic suppurative otitis media (CSOM) at the species level and analyze the morphology and antifungal susceptibility profiles of the three species.MethodThe sequencing of the internal transcribed spacer (ITS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 28 publications
(31 reference statements)
0
3
0
Order By: Relevance
“…Concerning the growth and morphological characteristics of the S. ciferrii complex, the fungus grows on Sabouraud dextrose agar (SDA) at different temperatures (22 • C, 27 • C, and 37 • C) after one week. Colonies are typically small, round, and milky-white-or cream-coloured, and can be hard, raised, and wrinkled or smooth [13,16,25,42]. Moreover, the S. ciferrii complex can grow on SDA with 0.1% cycloheximide, SDA with olive oil overlay, or 10% NaCl [36].…”
Section: Morphology and Identification Of S Ciferrii Complexmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the growth and morphological characteristics of the S. ciferrii complex, the fungus grows on Sabouraud dextrose agar (SDA) at different temperatures (22 • C, 27 • C, and 37 • C) after one week. Colonies are typically small, round, and milky-white-or cream-coloured, and can be hard, raised, and wrinkled or smooth [13,16,25,42]. Moreover, the S. ciferrii complex can grow on SDA with 0.1% cycloheximide, SDA with olive oil overlay, or 10% NaCl [36].…”
Section: Morphology and Identification Of S Ciferrii Complexmentioning
confidence: 99%
“…However, in the relatively few clinical reports available in the specific literature [17][18][19][20][21][22], this grouping was often not taken into account so that in various types of clinically documented fungal infections, species investigations were not performed [21][22][23][24] and the isolated fungal agent was indicated using various and non-univocal terminology. Identifying the S. ciferrii complex at the species level is of great importance in epidemiological studies and for the management of empirical antifungal therapy [25]. However, limiting data concerning the epidemiological, etiologic, and clinical aspects of the S. ciferrii complex are reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…animal and clinical strains exhibited notable reduced uconazole susceptibility with minimal inhibitory concentration [MIC] values ranging from 32 to 128 mg/L) [3].…”
mentioning
confidence: 99%
“…Gene annotation results of T. ciferrii strain CBS 4856 were used to train a new de novo prediction model for AUGUSTUS v3.3.2 and then utilized for structural annotation of our C. mucifera genome [11], and a total of 6533 genes were predicted. Due to the "intrinsically" reduced uconazole susceptibility in C. mucifera and other species of the T. ciferrii complex [3], we conducted an mutation analysis of the azole target Erg11p. We observed that position 499 of Erg11p amino acid sequence in C. mucifera isolate 17G1312 (GenBank accession no.…”
mentioning
confidence: 99%
See 1 more Smart Citation